Characterization of surface oil thickness distribution patterns observed during the Deepwater Horizon (MC-252) oil spill with aerial and satellite remote sensing. Issue 1 (15th September 2016) - Svejkovsky, Jan; Hess, Mark; Muskat, Judd; Nedwed, Tim J.; McCall, Jenifer; Garcia, Oscar
Abstract: Knowledge of the spatial distribution of oil thickness patterns within an on-water spill is of obvious importance for immediate spill response activities as well as for subsequent evaluation of the spill impacts. For long-lasting continuous spills like the 2010 3-month Deepwater Horizon (DWH) event in the Gulf of Mexico, it is also important to identify changes in the dominant oil features through time. This study utilized very high resolution (≤ 5 m) aerial and satellite imagery acquired during the DWH spill to evaluate the shape, size and thickness of surface oil features that dominated the DWH slick. Results indicate that outside of the immediate spill source region, oil distributions did not encompass a broad, varied range of thicknesses. Instead, the oil separated into four primary, distinct characterizations: 1) invisible surface films detectable only with Synthetic Aperture Radar imaging because of the decreased surface backscatter, 2) thicker sheen & rainbow areas (< 0.005 mm), 3) large regional areas of relatively thin, "metallic appearance" films (0.005–0.08 mm), and 4) strands of thick, emulsified oil (> 1 mm) that were consistently hundreds of meters long but most commonly only 10–50 m wide. Where present within the slick footprint, each of the three distinct visible oil thickness classes maintained its shape characteristics both spatially (at different distances from the source and in different portions of the slick), and temporally (from mid-May through July 2010). The region over the source site tended to contain a more continuous range of oil thicknesses, however, our results indicate that the continuous injection of subsurface dispersants starting in late May significantly altered (lowered) that range. In addition to characterizing the oil thickness distribution patterns through the timeline of one of the world's largest oil spills, this paper also details the extension of using high resolution aerial imagery to calibrate medium resolution satellite data sources such as USA's Thematic Mapper (30 m) to provide larger-scale spatial views of major spills, and discusses implications for utilizing such data for oil spill characterizations and spill response. Highlights: Outside the spill source region oil existed in four distinct thickness classes. Thickness classes maintained their shape characteristics spatially and temporally. Subsurface dispersant injections lowered fresh oil thickness around the source site. Medium resolution satellite data was calibrated with high resolution aerial images. Calibrated satellite images yielded oil volume distributions over most of the spill.